2020
DOI: 10.1021/acsaem.9b02371
|View full text |Cite
|
Sign up to set email alerts
|

Designing Tailored Gas Diffusion Layers with Pore Size Gradients via Electrospinning for Polymer Electrolyte Membrane Fuel Cells

Abstract: We present electrospinning as a versatile technique to design and fabricate tailored polymer electrolyte membrane (PEM) fuel cell gas diffusion layers (GDLs) with a pore-size gradient (increasing from catalyst layer to flow field) to enhance the high current density performance and water management behavior of a PEM fuel cell. The novel graded electrospun GDL exhibits highly robust performance over a range of inlet gas relative humidities (RH). At relatively dry (50% RH) inlet conditions that exacerbate ohmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 67 publications
2
38
0
Order By: Relevance
“…On the other hand, it is of interest to assess how controlled grading of the pore structure can influentially impact the improvement of the overall transport kinetics of porous materials. This can be useful for classical electrochemical processes [43]. It is, therefore, important to better understand the correlation between structure and transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is of interest to assess how controlled grading of the pore structure can influentially impact the improvement of the overall transport kinetics of porous materials. This can be useful for classical electrochemical processes [43]. It is, therefore, important to better understand the correlation between structure and transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…[13,[23][24][25][26][27] In regard to microstructure, a growing body of work focuses on developing interconnected pores across multiple length scales to balance kinetics and mass transport, [28] either by fabricating thinner electrospun fiber scaffolds [29] with directional fiber alignment [30,31] or generating architectures with multitudes of pore sizes. [32][33][34][35] Advanced numerical simulations on porous media have demonstrated that streamwise-oriented fibers and pores can lead to increased permeabilities and improved dispersion efficiency; [36] furthermore, material sets possessing wide variability in pore sizes with high specific surface area induce higher dispersion and reaction rates, improving overall performance. [37][38][39][40][41] Collectively, these prior works constitute important advances in the electrochemical science and engineering of porous electrodes.…”
mentioning
confidence: 99%
“…The simulations illustrate that the invading fingers of the liquid water become thinner as the liquid advances in the porous medium the medium, from a collaborative pore filling behaviour, with clusters of the size of few pores d f (x∕L pm ∼ 0.5) ∼ 4r p , to a preferential flow along a single pore, when d f (x∕L pm = 1) ∼ 2r p , as more and more pore throats contribute to impede liquid transport along the direction of the flow. Interestingly, this finding motivates a possible new design of GDLs, as characterized by an increasing size of the pore diameters, as a recent study also suggested (Balakrishnan et al 2020). Such a design should promote the water transport in the GDL by decreasing the capillary pressure thresholds, induced by the pore throats, along the flow direction.…”
Section: The Structure Of the Liquid Phase Emerging From The Gdlmentioning
confidence: 77%
“…Within the pores and interstices of the GDL porous microstructure, the reactant gas and the produced water flow to and from the catalyst layer. The GDL is the key component for regulating the transport phenomena inside the cell and, in turn, its design is an important factor to determine cell performance (Majlan et al 2018;Balakrishnan et al 2020). In particular, the GDL porous microstructure is fundamental in determining the two-phase (liquid-gas) dynamics and distribution in the cell, a complex mechanism of mass transport that affects the management of the produced water (Berg et al 2004).…”
Section: Introductionmentioning
confidence: 99%